A Shorter Circular Stapler Height at the Gastrojejunostomy during a Roux-En-Y Gastric Bypass Results in Less Strictures and Bleeding Complications. (29th May 2018) - Horkoff, Michael; Purich, Kieran; Switzer, Noah; Prasad, Shalvin; Church, Neal; Shi, Xinzhe; Mitchell, Philip; Debru, Estifanos; Karmali, Shahzeer; Gill, Richdeep
Abstract : The laparoscopic Roux-en-Y gastric bypass (LRYGB) is prone to a number of complications, most notably at the gastrojejunostomy (GJ) staple line. The circular stapler technique is a common method used to create the GJ anastomosis. Although recent studies have shown a decreased rate of anastomotic strictures with shorter stapler heights, the optimal circular stapler height to use remains controversial. We therefore completed a retrospective cohort study within the Alberta Provincial Bariatric Program (APBP) to compare outcomes between the 3.5 mm and 4.8 mm stapler heights. We identified 215 patients who had a LRYGB done between the years 2015 and 2017. 143 patients had the GJ constructed with a 3.5 mm circular stapler height, with the remaining 72 patients having the GJ fashioned with a 4.8 mm stapler height. The rate of anastomotic stricturing was lower in the 3.5 mm stapler group compared to the other cohort (3.5 versus 13.9%, resp., p = 0.008 ). Likewise, the overall rate of bleeding complications was lower in the 3.5 mm stapler group compared to the 4.8 mm group (6.3 versus 15.3%, resp., p = 0.04 ). The rate of anastomotic stricturing and postoperative bleeding is lower with the use of a 3.5 mm circular stapler compared to a 4.8 mm circular stapler when forming the GJ.